Is it Time to Adopt Alternate Teaching Strategy? - Joshi, S (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.3126/joim.v34i2.9042 Journal of Institute of Medicine August, 2012; 34:2 1-3